Date: Dec 4, 2012 4:22 PM
Author: Virgil
Subject: Re: Cantor's first proof in DETAILS

In article 
"Ross A. Finlayson" <> wrote:

> And, m > n implies EF(m) > EF(n), because here m > n. It is true,
> that. The functions there modeling it are all constant monotone
> increasing, and they all go to one.

IN your origin definitions, you had EF_n(m) = 1/n, for 1 <= m <= n,
so that SUM_(x=1..n) EF_n(x) = 1, for all n and then defined you EF()
also the limit function of the EF_n() as n -> oo.

That did not work then and does not work now.